An Integrated Pan-Cancer Analysis of 33 Human Cancers Reveals the Potential Clinical Implications and Immunotherapeutic Value of C-X-C Motif Chemokine Ligand 13 - Zhang, Huanyu; Yin, Honghao; Chen, Jing; Yuan, Yuan (Frontiers in Oncology, 2022)
Background C-X-C Motif Chemokine Ligand 13 (CXCL13) plays a crucial part in the pathogenesis of numerous lymphoproliferative disorders, inflammatory responses, and autoimmune diseases. CXCL13 also influence tumor development and prognosis, and be a potential target for cancer treatment. However, CXCL13 expression-based panoramic picture in pan-cancer remain unclear. This study focused on elucidating different expression levels, prognostic significance, immune-related characteristics, epigenetic variations, and immunotherapeutic value of CXCL13. Methods Based on different databases such as TCGA, GTEX, CCLE and HPA, we studied the expression of CXCL13 in different tissues at different levels. Moreover, we analyzed the correlation between CXCL13 expression and clinicopathological characteristics, prognosis, Mismatch Repair Genes (MMRs), Microsatellite Instability (MSI), tumor mutation burden (TMB), immune cells infiltration, immune-related genes, and the role in tumor immunotherapy. And the expression of CXCL13 in digestive tract cancers and the correlation between CXCL13 and immune genes were further analyzed by histological verification. Results CXCL13 was highly expressed in various tumor tissues and was also closely related to prognosis. CXCL13 expression levels were closely related to MSI, TMB and immune cells infiltration, including CD8+ T cells, macrophages, follicular helper T cells and B cells. CXCL13 expression levels were related to immune checkpoint genes and the efficacy of immunotherapy. Conclusion CXCL13 might be a useful biomarker for determining the diagnosis and prognosis of human cancers but also a biomarker for evaluating the efficacy of immunotherapy.